Changes in species compositions of fish in the bays of the Northwestern Gulf of Mexico - Torres Ceron, Milton; Fujiwara, Masami; Martinez-Andrade, Fernando (Frontiers in Marine Science, 2023)
To investigate the effects of climate change and other environmental factors on coastal marine fish communities in the subtropics, spatiotemporal differences in the compositions of fish species in the bays of the northwestern Gulf of Mexico were analyzed. We used fish count data collected using gillnets in eight major bays, encompassing over 600 km of coastline, during spring and fall seasons from 1982 to 2019. The nonmetric multidimensional scaling (NMDS) on the Bray-Curtis dissimilarity index among species composition vectors was used to detect the differences in species composition, and the similarity percentages (SIMPER; Clarke 1993) were used to determine the contribution of species to the differences. The result shows there was a gradual change in species composition in all bays over the years, and the composition was different among bays and seasons. The species contributing to the temporal changes included those that are expanding, such as Common snook (Centropomus undecimalis) and Smallscale fat snook (C. parallelus), as well as retracting their distributions toward the north, such as Southern flounder (Paralichthys lethostigma) and Spanish mackerel (Scomberomorus maculatus). The species observed only in recent years in these bays, such as Gulf pipefish (Syngnathus scovelli) and Chain pipefish (S. louisianae), tended to have a preference for warmer water. These results are consistent with the potential effects of climate change. The spatial salinity gradient has a substantial impact on species compositions. Because the salinity of the bays in the study area generally exhibits an increasing trend from the northern to southern bays, it is causing spatial variations in species composition. This indicates that spatiotemporal species distributions are influenced by multiple environmental conditions, including those changing over time such as temperature, and those changing over space such as salinity. This complexity makes our ability to accurately predict future species compositions under changing environmental conditions challenging.